Web-based Application for Visual Representation of Learners' Problem-Posing Learning Pattern - Supianto, Ahmad Afif; Wicaksono, Satrio Agung; Bachtiar, Fitra A.; Herlambang, Admaja Dwi; Hayashi, Yusuke; Hirashima, Tsukasa (Faculty of Computer Science (FILKOM) Brawijaya University, 2019)
Students’ learning process analysis normally involves massive amount of data. This study explores the pattern and relationship of students’ learning process data in an interactive learning media to identify their learning process patterns to ease the needs of sophisticated data analysis for class instructors and educational researchers. This study focuses on the development of a web-based software application that creates a visual representation of students’ learning process in a learning media. The result of this software is a visualization of students’ activity sequence. This result is then used to infer students’ learning patterns as well as identifying their learning behavior and to create a better feedback via the learning instructors. As a case study, this research uses the data log of Monsakun, a digital learning environment that focuses on the subject of mathematic for grade school students on the topic of arithmetic using story-based question and problem-posing approach. Investigation result shows four distinct learning activity patterns which are: smart pattern, adventure pattern, peer pattern and cyclic pattern. Each pattern requires different feedback to optimize learning progression, by using this web-based application, appropriate feedback to specific learning pattern is then applied to each student based on its learning activity pattern.